2012
DOI: 10.1177/0886260512454722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type and Severity of Intimate Partner Violence on Women’s Health and Service Use

Abstract: Intimate partner violence (IPV) has major affects on women's wellbeing. There has been limited investigation of the association between type and severity of IPV and health outcomes. This article describes socio-demographic characteristics, experiences of abuse, health, safety, and use of services in women enrolled in the Women's Evaluation of Abuse and Violence Care (WEAVE) project. We explored associations between type and severity of abuse and women's health, quality of life, and help seeking. Women (aged 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
108
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 41 publications
12
108
1
2
Order By: Relevance
“…Our study also extends prior research to show how such interaction affects the severity of depressive symptoms. Furthermore, studies have demonstrated the association of depression with low social support among women exposed to IPV (Hegarty et al, 2013; Mburia-Mwalili et al, 2010). Our study extends the literature by strongly suggesting social support interacts with IPV exposure, and that even women with high social support are vulnerable to the effects of recent IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also extends prior research to show how such interaction affects the severity of depressive symptoms. Furthermore, studies have demonstrated the association of depression with low social support among women exposed to IPV (Hegarty et al, 2013; Mburia-Mwalili et al, 2010). Our study extends the literature by strongly suggesting social support interacts with IPV exposure, and that even women with high social support are vulnerable to the effects of recent IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados extienden trabajos previos en los que predomina sintomatología propia de un trastorno de ansiedad, distimia, somatización, depresión, desconfianza, suspicacia del entorno y estrés postraumático (Amor et al, 2002;Calvete et al, 2007;Davins, 2005;Hegarty et al, 2013;Labrador et al, 2010;Lacey et al, 2013;Sarasua et al, 2007). Asimismo, en las escalas de personalidad del MCMI-III aparece la puntuación media más elevada en el prototipo Compulsivo.…”
Section: Discussionunclassified
“…Entre los factores que predicen la aparición de sintomatología asociada al maltrato se encuentran la frecuencia, severidad y duración de la violencia vivida, interviniendo variables personales como la existencia de victimización previa, edad, estabilidad emocional, recursos psicológicos, apoyo social, etc. (Hegarty et al, 2013). De ahí la relevancia de considerar la influencia de diversas variables de análisis en el impacto psicológico de la violencia de pareja.…”
unclassified
“…The sample thus included women from all the different stages identified in the transtheoretic model of change or other readiness to change models (Burke, Mahoney, Gielen, McDonnell, & O'Campo, 2009;Chang, et al, 2006). The health of the women was poorer than that of women who did not screen positive for fear of a partner (Hegarty, et al, 2013a).…”
Section: Insert Table 1 About Herementioning
confidence: 99%